PERAN AUDIT INTERNAL DALAM UPAYA PREVENTIF FRAUD (STUDY KASUS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI) - Alfian, Nurul; Rahayu, Runik Puji (JURNAL AKUNTANSI DAN INVESTASI, 2019)
Generally fraud prevention is only done on companies that have good internal control, but internal auditors also have an important role in the company, especially in terms of preventing fraud, internal audits are tasked with checking all parts or in the company whether they are in accordance with predetermined standards or not, and find solutions to problems that occur within the company.This research is a qualitative descriptive study, which describes the data obtained from the banking company's annual report. The population of this research is banking companies listed on the IDX while the sample uses purposive sampling which produces four banking companies, namely, BNI, BRI, BTN, Bank Mandiri. In this study researchers used descriptive methods, where researchers describe or explain data obtained about the role of internal uadit in preventing fraud and comparing fraud prevention by auditors and what efforts have been made by banking companies in preventing fraud.Internal audit has a very important role in preventing fraud. The internal audit of the four banks that were sampled was able to implement and carry out the prepared audit plan and provide recommendations that could solve the problems that occurred in that manner. All audit activities have been included in the audit charter and are governed by the directors' regulations. Of the four banks, there have been efforts in preventing fraud, among others, by providing a Whistleblowing system and a program to control gratification. For employees or other parties who commit fraud (fraud), sanctions are categorized into 3 types, namely minor, moderate and severe sanctions and sanctions in the form of administrative sanctions and financial sanctions.